Numb inhibits membrane localization of Sanpodo, a four-pass transmembrane protein, to promote asymmetric divisions in Drosophila. - O'Connor-Giles, K.M.; Skeath, J.B. (Developmental Cell, 2003)
Cellular diversity is a fundamental characteristic of complex organisms, and the Drosophila CNS has proved an informative paradigm for understanding the mechanisms that create cellular diversity. One such mechanism is the asymmetric localization of Numb to ensure that sibling cells respond differently to the extrinsic Notch signal and, thus, adopt distinct fates (A and B). Here we focus on the only genes known to function specifically to regulate Notch-dependent asymmetric divisions: sanpodo and numb. We demonstrate that sanpodo, which specifies the Notch-dependent fate (A), encodes a four-pass transmembrane protein that localizes to the cell membrane in the A cell and physically interacts with the Notch receptor. We also show that Numb, which inhibits Notch signaling to specify the default fate (B), physically associates with Sanpodo and inhibits Sanpodo membrane localization in the B cell. Our findings suggest a model in which Numb inhibits Notch signaling through the regulation of Sanpodo membrane localization.